2022
DOI: 10.46747/cfp.6810721
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mobilization for primary care

Abstract: In hospitals diseases stay and people come and go; in general practice people stay and diseases come and go. Iona Heath 1T he Rourke Baby Record (RBR): why and how has this practice tool survived and maintained its clinical relevance and academic rigour? In this article we share lessons learned in knowledge mobilization (KM) and clinical uptake (Box 1).In contrast to single-issue or single-disease guidelines, the RBR is deeply rooted in the broad continuity-of-care realities of general or family practice, as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Although efforts to improve diversity among medical students started in the 1970s, specialty-specific studies on diversity progression began to appear in the late 1980s and the 1990s . Starting in the early 1980s, several studies in various medical fields, including general surgery, dermatology, and family medicine, have revealed significant differences in gender and racial diversity within specialties . Furthermore, some studies have demonstrated sex disparities between surgical and nonsurgical specialties …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although efforts to improve diversity among medical students started in the 1970s, specialty-specific studies on diversity progression began to appear in the late 1980s and the 1990s . Starting in the early 1980s, several studies in various medical fields, including general surgery, dermatology, and family medicine, have revealed significant differences in gender and racial diversity within specialties . Furthermore, some studies have demonstrated sex disparities between surgical and nonsurgical specialties …”
Section: Introductionmentioning
confidence: 99%
“…Despite the demonstration of a lack of diversity over the last 40 years and numerous organizations, including the Association of American Medical Colleges (AAMC), speaking to this issue, progress has been relatively slow in several medical fields. Over the last 20 years, numerous recurrent studies within the fields of academic medicine, including general surgery, family medicine, and orthopedic surgery, have found the same lack of representation as that found in the 1980s when these studies began . Therefore, a different approach using diversity of leadership could be helpful in transforming academic medicine into a more diverse field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to increasing minority and female representation among physicians is topdown diversity, which includes using diversification of leadership to diversify the workforce [24][25][26][27][28][29][30] . Diverse representation has not been uniform across sectors of the medical profession, despite the improvements in diversity among medical students [31][32][33][34][35][36][37][38][39][40][41][42][43][44] .Orthopaedic surgery has demonstrated some of the most substantial gaps in racial and gender representation and has frequently "lagged" behind other surgical and nonsurgical specialties 11,35,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . In the early 2000s, the American Academy of Orthopaedic Surgeons (AAOS) and the American Orthopaedic Association (AOA) made commitments to improving leadership Disclosure: The Disclosure of Potential Conflicts of Interest forms are provided with the online version of the article (http://links.lww.com/JBJS/H34).…”
mentioning
confidence: 99%
“…Another approach to increasing minority and female representation among physicians is topdown diversity, which includes using diversification of leadership to diversify the workforce [24][25][26][27][28][29][30] . Diverse representation has not been uniform across sectors of the medical profession, despite the improvements in diversity among medical students [31][32][33][34][35][36][37][38][39][40][41][42][43][44] .…”
mentioning
confidence: 99%